Polymer Coatings. - De With, Gijsbertus (John Wiley & Sons, Incorporated, 2018)
The book provides a practice-oriented overview of the fundamentals of polymer coatings. The readers learn about the different classes of materials in use, namely polymers and polymer networks, thermoset plastics, alternative chemicals like solvent- and water-based coatings, and a variety of additives. Dedicated chapters present deposition methods encompassing several mechanical and electrochemical coating approaches, in addition to physical-chemical aspects of the coating process. The wealth of currently available characterization methods is covered in a separate chapter which treats spectroscopic, morphological, thermal and mechanical techniques. The second part of the book is devoted to different selected topics which have undergone strong developments in recent years, such as electrically conductive coatings, hydrophobic and hydrophilic paints, and self-replenishing coatings. Finally, the author summarizes the present status of the research field, describes systems currently under investigation and draws our attention to systems that have not been explored yet.